Dopaminergic agents and nutritional status in Parkinson's disease. Issue 12 (12th September 2014) - Laudisio, Alice; Vetrano, Davide L.; Meloni, Eleonora; Ricciardi, Diego; Franceschi, Francesco; Bentivoglio, Anna Rita; Bernabei, Roberto; Zuccalà, Giuseppe
Abstract Background Malnutrition has been found in up to 24% of patients with Parkinson's disease; dopaminergic drugs might impair nutritional status. We evaluated the association of nutritional status with the use of dopaminergic agents. Methods We analyzed data from 75 elderly patients with Parkinson's disease attending a geriatric day hospital. Nutritional status was assessed by the Mini Nutritional Assessment (MNA). Dopaminergic drugs were normalized for weight. Results In linear regression, total levodopa (l‐dopa) equivalent daily dose (LEDD) was associated with worse MNA (B = −0.14, 95% CI = −0.26‐−0.02; P = 0.019). This association remained significant only for l‐dopa (B = −0.19, 95% CI = −0.32‐−0.52; P = 0.007), but not dopaminergic agent dosages. Increasing l‐dopa dosages were associated with increasing probability of risk of malnutrition (P for trend = 0.049). Conclusions In our population, LEDD was associated with worse nutritional status and risk of malnutrition; this association was limited to use of l‐dopa. © 2014 International Parkinson and Movement Disorder Society